KONSUMSI, KEBUTUHAN DAN KECUKUPAN BERAS NASIONAL TAHUN 2002 – 2007 - Aris Zaenal Muttaqin; Drajat Martianto (Food and Nutrition Society of Indonesia, 2009)
The study aimed to estimate national rice consumption, total rice demand, and national rice adequacy in 2002-2007. Secondary data such as household rice consumption in 2002-2007 based on SUSENAS data, government rice consumption (distribution of raskin in 2002-2007), and national rice availability in 2002-2007 based on food balance sheet in 2002-2007. National rice consumption, based on estimation, was 28,317,272 tons or 134.4 Kg/cap (in 2002), 28,135,078 tons or 128.4 Kg/cap (in 2005), and 27,050,183 tons or 120.2 Kg/cap (in 2007). National rice requirement, based on estimation, was 31,900,529 tons or 151.5 Kg/cap (in 2002), 31,760,865 tons or 144.9 Kg/cap (in 2005), and 30,618,665 tons or 136.0 Kg/cap (in 2007). Rice availability coming from domestic production (without import) was deficit in 2002 and 2005. Domestic rice availability was surplus in 2007 (5.9 %).